Implementasi Realisasi Kredit Lembaga Keuangan Mikro: (Studi Kasus Pada Koperasi Syirkah BMT Sunan Kalijogo Malang) - Doni Teguh Wibowo (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2016)
Microfinance institutions are a sector that must be developed and utilized optimally in order to achieve equal distribution of people's income. The purpose of this study is to determine the implementation of effective and efficient credit realization to increase profits. The research method used is the explanatory method. The results showed that the implementation of credit at the BMT Sunan Kalijogo Syirkah Cooperative was not effective and efficient. This is evidenced by the rise and fall in the value of profitability which also affects the rise and fall in the value of credit realization. In calculating the NPL ratio, it reached 32.58% in 2011 with the lowest NPL value of 17.85%, so that the average NPL ratio is still at 31.22% annually. The calculation of the BOPO ratio reached 95.86% in 2012 with the smallest ratio in 2011 of 77.11%, so that the average BOPO ratio is still 88.26% every year, which means that operational activities are still not efficient. Whereas the value of the profitability ratio reached the highest in 2014 of 4.92%, while for the value of the smallest profit ratio in 2015 which reached a figure of 1.38%, the size of this profitability ratio shows operating expenses which are influenced by current loans and credit traffic jams impacting revenue. The conclusion of this study is that an increase in the NPL ratio can increase the value of BOPO and decrease the value of the Profitability ratio. Suggestions for this research are to improve management performance in collecting third party funds and increase the principle of prudence towards prospective customers and through diversification of customer portfolios.